“Anna Karenina” And Lev Nikolaevich Tolstoy - Kurbanova M.O; Mamadalieva Noila; Zufarova Khurshida; Turgunova Gulchira (Zien Journals, 2022)
The article highlights the largest social novel by L.N. Tolstoy "Anna Karenina", in which it has, in the most essential, namely, in the ideological enrichment of the original idea, a creative history typical of great works of the great writer by the direct influence of Pushkin. The portraits of secondary heroes of the novel are considered from the standpoint of their role and in the ideological structure of the work. The idea of lack of spirituality, carried out by the writer through these portrait characteristics, as well as the principle of the work of portraits of minor characters to deepen the images of the main characters, is analyzed.
Keywords: major; social; novel; significant